Co-Release of GABA Does Not Occur at Glycinergic Synapses onto Lumbar Motoneurons in Juvenile Mice - Bhumbra, Gardave S.; Moore, Niall J.; Moroni, Mirko; Beato, Marco (Frontiers in Cellular Neuroscience, 2012)
The fast inhibitory neurotransmitters glycine and GABA are co-localised in synaptic terminals of inhibitory interneurons in the spinal cord and co-released onto lumbar motoneurons in neonatal rats. We performed whole cell voltage-clamp experiments on spinal cord preparations obtained from juvenile (P8 - 14) mice to determine whether inhibitory currents exhibited GABAergic components in motoneurons of animals of weight-bearing age. Subsequently we established whether or not GABA is co-released at glycinergic synapses onto motoneurons by determining if it conferred modulatory effects on the kinetics of glycinergic currents. Exponential fitting analysis showed that evoked and miniature inhibitory post-synaptic currents (IPSCs) were best-fitted with a single decay time constant. Responses recorded from connected interneuron-motoneuron pairs showed no effect of a benzodiazepine or a GABAA receptor antagonist. Similarly IPSCs evoked by extracellular stimulation and miniature IPSCs were not affected by either agent, indicating the absence of co-detection. Experimental manipulation of the relative content of pre-synaptic GABA and glycine conferred no effect on post-synaptic responses. It is thus unlikely that GABA is co-released in biologically relevant amounts at glycinergic synapses onto lumbar motoneurons in mice of this age.